The kinetics of the active and de-energized transport of O-methyl glucose in Ustilago maydis - Miller, D. M.; Harun, Salleh (Elsevier, 1978)
The kinetics of the uptake and efflux of 3-0-methyl-glucose in sporidia of Ustilago maydis were measured, both in active cells and in cells whose metabolic activity had been inhibited by azide and iodoacetate. The de-energized transport system proved to be carrier mediated with apparent affinity constants 13 ± 2 mM outside (Ko) and 18 ± 2 mM inside (1\)). The apparent maximum rate constants for the same system were 0.66 ± 0,05 mmo l/l cell water per min for uptake (11+) and 0.53 ± 0.04 mmo l/l cell water' per mill for efflux (11_), For the active system Ko = 0,08 ± 0,01, K) > 40, \I, = 9.7 :':0,5 and V_ = l.lt 0.9 (in equivalent units). These results are discussed in the context of the carrier mechanism as proposed by Regen and Morgan (Regen, D.M. and Morgan, H, E, (1964) Biochim. Biophys. Acta 79, 151-166). The antifungal compound carboxin had no effect on de-energized transport hut was shown to decrease both Ko and 11+in the active system. Phloretin and phlorizin were also found to be without effect on de-energized cells but the former enhanced while the latter inhibited active uptake.